2014
DOI: 10.1063/1.4865946
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the exchange-correlation functional on H2 dissociation on Ru(0001)

Abstract: The specific reaction parameter (SRP) approach to density functional theory (DFT) has enabled a chemically accurate description of reactive scattering experiments for activated H 2 -metal systems (H 2 + Cu(111) and Cu(100)), but its application has not yet resulted in a similarly accurate description of non-activated or weakly activated H 2 -metal systems. In this study, the effect of the choice of the exchange-correlation functional in DFT on the potential energy surface and dynamics of H 2 dissociation on Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
191
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(210 citation statements)
references
References 110 publications
16
191
0
Order By: Relevance
“…The model also does not yield the minimum reaction barrier height (E b ), which would be useful for testing new electronic structure methods that are potentially more accurate than the present state-of-the-art method for computing potential energy surfaces (PESs) for molecule−metal surface reactions (density functional theory (DFT) at the generalized gradient approximation (GGA) level). 32 The DFT-GGA method is known to yield E b with an accuracy no better than 5 kcal/mol for gas-phase reactions, 33 with GGA functionals both underestimating and overestimating E b for gas−metal surface reactions, 34 while adsorption energies on metal surfaces exhibit similar lack of accuracy. 35 An accurate value of E b is also relevant to accurately modeling the steam reforming reaction over a Pt(111) surface as kinetics calculations of rates of heterogeneously catalyzed processes require reaction barrier heights as input parameters.…”
mentioning
confidence: 99%
“…The model also does not yield the minimum reaction barrier height (E b ), which would be useful for testing new electronic structure methods that are potentially more accurate than the present state-of-the-art method for computing potential energy surfaces (PESs) for molecule−metal surface reactions (density functional theory (DFT) at the generalized gradient approximation (GGA) level). 32 The DFT-GGA method is known to yield E b with an accuracy no better than 5 kcal/mol for gas-phase reactions, 33 with GGA functionals both underestimating and overestimating E b for gas−metal surface reactions, 34 while adsorption energies on metal surfaces exhibit similar lack of accuracy. 35 An accurate value of E b is also relevant to accurately modeling the steam reforming reaction over a Pt(111) surface as kinetics calculations of rates of heterogeneously catalyzed processes require reaction barrier heights as input parameters.…”
mentioning
confidence: 99%
“…In this respect, gas-surface dynamics simulations are a powerful tool to explore this issue and, hence, to test the performance of any xc-functional in describing short-and long-range interactions. Previous gas-surface simulations of H 2 on Ru(0001), 30,59 H 2 on Cu(111), 15,16 and the above mentioned N 2 on W surfaces 37 have revealed the limitations of existing (non-empirical) semilocal xc-functionals in describing at the same foot regions of small and large density gradients. Therefore, an additional outcome of our present study is that the comparative analysis of the AIMD results will serve us to test the adequacy of different vdW-functionals in describing the multi-configurational space that rules the N 2 -W(110) interaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been found that only functionals that incorporate the vdW interaction are able to reasonably well reproduce the width of the initial sticking probability curve as a function of incidence energy. 30 The desorption of CO from Ru(0001) is another recent example pointing to the vdW interaction as a crucial ingredient in understanding this process. 31,32 The discrepancy between theory and experiments found when comparing the sticking coefficient S 0 , i.e., the dissociation probability at zero coverage, for various incident conditions (angle Θ i and kinetic energy E i ) of N 2 on W(110) is another appealing case for which vdW may play a prominent role.…”
Section: Introductionmentioning
confidence: 99%
“…In the search of a SRP functional for this system, we have considered functionals that mimic the van der Waals (vdW) interaction [56], motivated by recent studies that demonstrated the improved description of two molecule-surface reactions achieved with vdW-corrected density functionals [57,58]. Note that traditional GGA functionals are not able to predict the long range dispersion interactions.…”
Section: Introductionmentioning
confidence: 99%